3(1+-0.5y)+4y=-7

Simple and best practice solution for 3(1+-0.5y)+4y=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1+-0.5y)+4y=-7 equation:


Simplifying
3(1 + -0.5y) + 4y = -7
(1 * 3 + -0.5y * 3) + 4y = -7
(3 + -1.5y) + 4y = -7

Combine like terms: -1.5y + 4y = 2.5y
3 + 2.5y = -7

Solving
3 + 2.5y = -7

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 2.5y = -7 + -3

Combine like terms: 3 + -3 = 0
0 + 2.5y = -7 + -3
2.5y = -7 + -3

Combine like terms: -7 + -3 = -10
2.5y = -10

Divide each side by '2.5'.
y = -4

Simplifying
y = -4

See similar equations:

| 5x+4y+9=0 | | x+16-64= | | x*(3x)^1/2 | | 3C^3-24= | | 2x-7/3=-3 | | 2x-7/7=-3 | | x-4/4=9 | | ((7x-1)^(1/2))^2 | | -3/42-x/53/4 | | 5x-20=-3x+68 | | 3y=(x-20) | | 61000+1.30x=19x | | 0.43=x*0.24 | | 1/5=2/3×w | | 1100+0.06x=0.11x | | 2x+6=3x+31 | | sin(x)=-0.48 | | 3h+10=13 | | 60=5x-100 | | 2x+9=5x-19 | | 4(x-9)-3(2x+5)=4.5(2x-15) | | 4(x-5)-3(2x+9)=1.5(2x-9) | | 0.5x-2(x-1)=-1.5x+2 | | y=32x-16x^2 | | 2.3(7-x)=-0.9(9-x) | | 3x+29=12-79 | | -9/(x-6)^2=0 | | y=4(2a+10b) | | -3(x-1)=10 | | 2x+11=5(x-1) | | A/-7=2 | | 19x-12x=26 |

Equations solver categories